Assessing Disaster Preparedness Among Select Children's Summer Camps in the United States and Canada. Issue 8 (August 2017) - Chang, Megan; Sielaff, Alan; Bradin, Stuart; Walker, Kevin; Ambrose, Michael; Hashikawa, Andrew
Abstract : Objective: Children's summer camps are at risk for multiple pediatric casualties during a disaster. The degree to which summer camps have instituted disaster preparedness is unknown. We assessed disaster preparedness among selected camps nationally for a range of disasters. Methods: We partnered with a national, web-based electronic health records system to send camp leadership of 315 camp organizations a 14-question online survey of disaster preparedness. One response from each camp was selected in the following order of importance: owner, director, physician, nurse, medical technician, office staff, and other. The results were analyzed using descriptive statistics. Results: A total of 181 camps responses were received, 169 of which were complete. Camp types were overnight (60%), day (21%), special/medical needs (14%), and other (5%). Survey respondents were directors (52%), nurses (14%), office staff (10%), physicians (5%), owners (5%), emergency medical technicians (2%), and other (12%). Almost 18% of camps were located >20 mi from a major medical center, and 36% were >5 mi from police/fire departments. Many camps were missing emergency supplies: car/booster seats for evacuation (68%), shelter (35%), vehicles for evacuation (26%), quarantine isolation areas (21%), or emergency supplies of extra water (20%) or food (17%). Plans were unavailable for the following: power outages (23%); lockdowns (15%); illness outbreaks (15%); tornadoes (11%); evacuation for fire, flood, or chemical spill (9%); and other severe weather (8%). Many camps did not have online emergency plans (53%), plans for children with special/medical needs (38%), methods to rapidly communicate information to parents (25%), or methods to identify children for evacuation/reunification with parents (40%). Respondents reported that staff participation in disaster drills varied for weather (58%), evacuations (46%), and lockdowns (36%). The majority (75%) of respondents had not collaborated with medical organizations for planning. Conclusions: A substantial proportion of camps were missing critical components of disaster planning. Future interventions must focus on developing summer camp-specific disaster plans, increasing partnerships, and reassessing national disaster plans to include summer camp settings. Abstract : Summer camps care for millions of healthy children and those with special needs each year. Summer camps are vulnerable to both manmade and natural disasters, with pediatric campers having unique physiologic and developmental characteristics that make them susceptible to harm during such events. The degree to which summer camps have instituted disaster preparedness is unknown. Our survey of camp leadership from 169 camps provides an assessment of emergency preparedness across a range of disasters among summer camps nationally.